2006
DOI: 10.1007/s10600-006-0046-1
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and carbohydrates from Capparis spinosa roots

Abstract: Capparis spinosa is a member of the Capparaceae family. Lipids and carbohydrates from this plant have not previously been studied. Only data from a study of the alkaloids, flavonoids, and glycosides have been published [1][2][3][4][5].Herein we report results from an investigation of lipids and carbohydrates from roots of C. spinosa growing in Xinjiang Autonomy Region of China. Lipids and carbohydrates were isolated successively from a single portion of raw material. Lipids were extracted from air-dried ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…The flower buds of this shrub have been used for distinct purposes since ancient times (Rodrigo et al, 1992;Matthäus and Özcan, 2002). Recently studies have reported on the properties and potential uses of its flower buds (capers), fruits (caperberries), seeds, young shoots and roots as food and medicine (Akgül and Özcan, 1999;Inocencio et al, 2000;Giuffrida et al, 2002;Rivera et al, 2003;Özcan and Aydin, 2004;Yili et al, 2006). Other studies have focused on the phytopathological use of the plant extracts (Al-Banna et al, 2003;Mansour et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The flower buds of this shrub have been used for distinct purposes since ancient times (Rodrigo et al, 1992;Matthäus and Özcan, 2002). Recently studies have reported on the properties and potential uses of its flower buds (capers), fruits (caperberries), seeds, young shoots and roots as food and medicine (Akgül and Özcan, 1999;Inocencio et al, 2000;Giuffrida et al, 2002;Rivera et al, 2003;Özcan and Aydin, 2004;Yili et al, 2006). Other studies have focused on the phytopathological use of the plant extracts (Al-Banna et al, 2003;Mansour et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Πολυσακχαρίτες: ημικυτταρίνες (2,7%), πηκτίνες (3,5%) αποτελούμενες ως επί το πλείστον από αραβινόζη, γλυκόζη και γαλακτόζη, καθώς και υδατοδιαλυτοί πολυσακχαρίτες (3%) που αποτελούνται κυρίως από αραβινόζη, ξυλόζη και γαλακτόζη. [199] Το μέγεθος των μπουμπουκιών της κάππαρης επηρεάζει, σύμφωνα με σχετικές έρευνες που έγιναν, τη χημική σύσταση του φυτού. Έτσι λοιπόν φαίνεται πως η περιεκτικότητα σε νερό και υδατάνθρακες αυξάνει με την αύξηση του μεγέθους, ενώ αντίθετα η ποσότητα φλαβονοειδών, τέφρας, μετάλλων, λιπιδίων και πρωτεϊνών μειώνεται.…”
Section: η δράση και ο ρόλος των ιασμονικώνunclassified